Unveiling the effects of nonviolent communication training on youth empathy - Batūraitė-Bunka, Aistė; Jurevičienė, Margarita; Skoczowsky-Danielsen, Gert (Social Welfare: Interdisciplinary Approach, 2024)
Nonviolent communication (NVC) is a model of communication approach, a method, a process, a mindset and a way of life, and was developed by Marshal Rosenberg. NVC offers tools that support the principle of nonviolence and empathic communication. Empathy can be important in promoting pro-environmental behavior (Kansky & Massarani, 2022), and the lack of empathy has been associated with antisocial behavior and reoffending (Bazemore & Stinchcomb, 2004).The study aims to reveal a self-perceived change in empathy of vulnerable and not vulnerable youth after NVC training.To conduct the research, a qualitative research methodology was chosen, applying a structured interview survey method. Researchers conducted 10-hour-long NVC trainings for vulnerable and non-vulnerable youth groups and participants were asked open-ended questions in writing. The study demonstrated the feasibility of and relevance to NVC training on (vulnerable) youths‘ empathic communication. Results of the study have revealed the positive effects of intervention on increasing empathy, self-empathy, and efforts to renounce violent communication.